Modeling progressive absorption of a hydride material particle submitted to hydrogen. (11th March 2021) - Bebon, Ludovic; Maynadier, Anne; Chapelle, David; Thiébaud, Frédéric
Abstract: The present study deals with the modeling of a single intermetallic powder particle likely to form reversibly a hydride material while submitted to hydrogen gas. These materials that make part of the so-called hydrogen solid storage family are one of the most employed media used in order to store hydrogen. During hydrogenation cycling, the initially coarse powder expanses due to hydrogen absorption and shrinks over hydrogen desorption. The powder granularity also decreases with the number of cycles but seems to stabilize to reach a mechanical limit. One plausible explanation is that large particles decrepitate into smaller ones because, only due to their geometry, they are less able to accommodate large volume changes and thus, internal stresses are higher than in small particles. This is the hypothesis we intend to discuss in the present work, hypothesis that has never been investigated, in our knowledge, from a mechanical point of view. Within the framework of a simple analytical model, several parameters (initial particle size, material behavior parameters …) are varied in order to evaluate their influence on the propensity of the particle to decrepitate. After introducing the context, the model that allows describing the fragile elastic mechanical response of a single spherical particle submitted to hydrogen is presented. Computed stress and strain along the radius of particles with different size or elastic properties lead to the main conclusion: considering a spherical particles made of an undamaged uniform elastic brittle two phase material is insufficient to evidence dependency of the mechanical response on the particle size. Consequently, this primary model is unable to validate our hypothesis, according which the limit size of decrepitating is driven by the mechanical accommodation of volume changes. This implies that a description of heterogeneities or geometric irregularities must be introduced to account for the phenomenon of particle size stabilization during decrepitating. After results are presented and discussed, opportunities to deepen the present analysis are proposed to account for physical observations of the decrepitating phenomenon, and are to be developed in forthcoming publications. Graphical abstract: Image 1 Highlights: Investigations on decrepitation during hydrogen absorption in metal hydride. Special attention to the modeling of absorption/desorption in a spherical particle. Study deals with the mechanical description during phase transformation. Continuum mechanics framework does not predict the limit size of particles.